2012
DOI: 10.1002/jts.21691
|View full text |Cite
|
Sign up to set email alerts
|

Optimism predicts resilience in repatriated prisoners of war: A 37‐year longitudinal study

Abstract: Resilience, exhibiting intact psychological functioning despite exposure to trauma, is one perspective as to why some people who are exposed to trauma do not develop symptoms. This study examines the prisoner of war experience to expand our understanding of this phenomenon in extreme cases of trauma such as prolonged captivity, malnourishment, and physical and psychological torture. The study examined the United States' longest detained American prisoners of war, those held in Vietnam in the 1960s through earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 30 publications
7
48
0
5
Order By: Relevance
“…During the Vietnam era, a total of 662 U.S. military personnel were captured, survived imprisonment, and were repatriated. Some prisoners successfully escaped or accepted early release ( n = 94), but a majority of the population ( n = 568) was repatriated in the spring of 1973 (Segovia, Moore, Linnville, Hoyt, & Hain, 2012). Personal reports (e.g., Risner, 1973) have described the highly stressful nature of war imprisonment in Vietnam, emphasizing the high levels of injuries and illnesses U.S. prisoners experienced during captivity.…”
mentioning
confidence: 99%
“…During the Vietnam era, a total of 662 U.S. military personnel were captured, survived imprisonment, and were repatriated. Some prisoners successfully escaped or accepted early release ( n = 94), but a majority of the population ( n = 568) was repatriated in the spring of 1973 (Segovia, Moore, Linnville, Hoyt, & Hain, 2012). Personal reports (e.g., Risner, 1973) have described the highly stressful nature of war imprisonment in Vietnam, emphasizing the high levels of injuries and illnesses U.S. prisoners experienced during captivity.…”
mentioning
confidence: 99%
“…Eighteen variables (9 physical and 9 psychological, Table 1) were each z-scored and then averaged together to develop an average physical rating, and an average psychological rating for each individual. These average z-scores were then correlated (Pearson) with five of the six identified variables (Segovia et al, 2012), and two additional variables (captivity-related medical problems, and sleep efficiency at repatriation) were included into the model-development process. An independent t-test was performed for officer/enlisted on these health ratings.…”
Section: Methodsmentioning
confidence: 99%
“…Background Segovia et al (2012) identified in a retrospective study of Vietnam repatriated prisoners of war medical/psychiatric data (recorded circa 1973) six variables were critical for those who were considered resilient 38 years later; because, they were free of any psychiatric diagnoses across repeated medical evaluations since repatriation in 1973. These variables were the following: officer status in favor over enlisted status, older at time of capture, less time in solitary confinement, low antisocial/psychopathic personality, low post-traumatic stress symptoms upon repatriation, and optimism with the latter accounting for the most variance (17%) in the findings.…”
mentioning
confidence: 99%
“…One factor that contributes to resilience is the experience or harnessing of positive emotions even in the midst of highly stressful, potentially life‐threatening events (Bonanno, 2004; Folkman & Moskowitz, ; Fredrickson et al., ; Ong, Bergeman, Bisconti, & Wallace, ; Waugh, ). Examples of coping strategies that predict resilience include using humor (Masten, ; Sliter, Kale, & Yuan, ), optimism (Anthony, ; Segovia, Moore, Linnville, Hoyt, & Hain, ), relaxation (Anthony, ; Park et al., ), and exploration of surroundings (Cohler, ).…”
Section: Resilience and Positive Emotionalitymentioning
confidence: 99%